In Vivo Photopolymerization: Achieving Detailed Conducting Patterns for Bioelectronics - Fredrik Ek; Tobias Abrahamsson; Marios Savvakis; Stefan Bormann; Abdelrazek H. Mousa; Muhammad Anwar Shameem; Karin Hellman; Amit Singh Yadav; Lazaro Hiram Betancourt; Peter Ekström; Jennifer Y. Gerasimov; Daniel T. Simon; et al. (Advanced Science, 2024)
Abstract Bioelectronics holds great potential as therapeutics, but introducing conductive structures within the body poses great challenges. While implanted rigid and substrate‐bound electrodes often result in inflammation and scarring in vivo, they outperform the in situ‐formed, more biocompatible electrodes by providing superior control over electrode geometry. For example, one of the most researched methodologies, the formation of conductive polymers through enzymatic catalysis in vivo, is governed by diffusion control due to the slow kinetics, with curing times that span several hours to days. Herein, the discovery of the formation of biocompatible conductive structures through photopolymerization in vivo, enabling spatial control of electrode patterns is reported. The process involves photopolymerizing novel photoactive monomers, 3Es (EDOT‐trimers) alone and in a mixture to cure the poly(3, 4‐ethylenedioxythiophene)butoxy‐1‐sulfonate (PEDOT‐S) derivative A5, resulting in conductive structures defined by photolithography masks. These reactions are adapted to in vivo conditions using green and red lights, with short curing times of 5–30 min. In contrast to the basic electrode structures formed through other in situ methods, the formation of specific and layered patterns is shown. This opens up the creation of more complex 3D layers‐on‐layer circuits in vivo.